HUBUNGAN POLA ASUH ORANG TUA DENGAN STATUS GIZI ANAK USIA TODDLER - Heri Triwibowo; Heni Frilasari; Devi Sinta Septiani (Universitas Pesantren Tinggi Darul Ulum, 2022)
Parenting is a pattern of interaction between children and parents that includes not only physical needs (eating, drinking, clothing, etc.) and psychological needs (affection or feelings) but also the norms prevailing in the community so that children can live in harmony with the environment. Nutritionis aprocess of using foods normally consumed by an organism through the process of digestion, absorption, transport, storage, metabolism, and expensive substances are not used to sustain life, growth and normal functioning of the organs, as well as resulting in energy. The purpose of this study was to determine the relationship between family upbringing with toddler-age children's nutritional status in Region Wates village in Mojokerto. This type of research is an analytic study with a cross-sectional research design. The number of samples taken in this study is 80 respondent sthrough random sampling method. With the use of questionnaire and observation data and using the Chi-Square test with SPSS, the error level of 5%(0.05) obtained values?? of 0.796?, where ?=0.769>0.05 then H1 is rejected or H0 is accepted. So there is no family parenting relationship with the nutritional status of children in the toddler-age region of Wates village in Mojokerto. Parents can provide appropriate parenting for the child's condition because every child is different in the provision of parenting. Keywords: Parenting, Nutritional status, Children.